TEST ONLINE PENDUKUNG KONSENTRASI UNGGULAN ARTIFICIAL INFORMATICS - Maimunah Maimunah; Dede Cahyadi; Arsyad Septa Kuncoro (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2015)
Advances in information technology has developed very rapidly over the years requires us to always move forward and follow the developments. we are required to constantly innovate to face the competition is rapidly increasing nowadays. On Higher Education Prog particularly artificialconcentration of test runs informatics systems still use a written test, which the lecturer made the exam according to powerful subjects. This study proposes a new system that exam application about specific online student concentration Artificial Informatics in Higher Education Prog, which is based online, as for research use analysis method to the study of literature (source written or online) and design method with an analysis of the running system to detect existing problems. About the online application is a program that will show the development of the existing technology, in order to improve the effectiveness of the process in terms of generating online about simplify the process of test questions online, quicklyand accurately.